LncRNA DILC is downregulated in osteoarthritis and regulates IL‐6 expression in chondrocytes. Issue 9 (8th May 2019) - Huang, Junfeng; Liu, Lijun; Yang, Jinxing; Ding, Jinglun; Xu, Xu
Abstract: Excessive production of interleukin 6 (IL‐6) is involved in the pathogenesis of osteoarthritis. It has been reported that long noncoding RNA (lncRNA) DILC inhibited IL‐6 to regulate liver cancer stem cells. Therefore, lncRNA DILC may also participate in osteoarthritis. We found that lncRNA DILC was downregulated, while IL‐6 was upregulated in plasma of osteoarthritis patients comparing to the control group. Levels of plasma lncRNA DILC and IL‐6 were significantly and inversely correlated only in patients with osteoarthritis. Downregulation of lncRNA DILC effectively distinguished patients with osteoarthritis from the control group. Overexpression of lncRNA DILC resulted in inhibited IL‐6 expression in chondrocytes, while treatment with exogenous IL‐6 did not affect lncRNA DILC expression. However, lncRNA DILC overexpression did not affect the proliferation and apoptosis of chondrocytes. Therefore, lncRNA DILC is downregulated in osteoarthritis and regulates IL‐6 expression in chondrocytes. Abstract : Long noncoding RNA (lncRNA) DILC is downregulated in patients with osteoarthritis. Overexpression of lncRNA DILC may serve as a potential therapeutic target for osteoarthritis by inhibiting IL‐6 expression in chondrocytes.